2016
DOI: 10.12740/pp/43486
|View full text |Cite
|
Sign up to set email alerts
|

Elective cesarean section on psychiatric indications – the phenomenon analysis, report of two cases and psychiatric clinical recommendations

Abstract: Antenatal care of women with mental disorders requires close cooperation between the obstetricians and psychiatrists specialised in the mental disorders due to somatic state. Such cooperation should lead to preventing both obstetric and psychiatric complications during the pregnancy and labour in women experiencing symptoms of mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Precious pregnancies of women with IVF conception, a high risk of placenta accreta ( 39 ) and, in some cases, the maternal age ( 40 ) constitute factors for ELCS. In our study, women with anxiety disorder or depression were more likely to have an EMCS, a comparable finding of similar studies ( 41 , 42 ) revealing a deficit in perinatal mental health services in Greece ( 43 , 44 ) as opposite to other European countries with low CS rates ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 90%
“…Precious pregnancies of women with IVF conception, a high risk of placenta accreta ( 39 ) and, in some cases, the maternal age ( 40 ) constitute factors for ELCS. In our study, women with anxiety disorder or depression were more likely to have an EMCS, a comparable finding of similar studies ( 41 , 42 ) revealing a deficit in perinatal mental health services in Greece ( 43 , 44 ) as opposite to other European countries with low CS rates ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 90%
“…Two groups of determinants of psychiatric indications for caesarean section can be distinguished [59].…”
Section: Psychiatric Indicationsmentioning
confidence: 99%
“…Several studies have shown that women with a history of anxiety disorder or depression, with or without psychiatric treatment, are more likely to be unable to cooperate during delivery or exhibit tokophobia and prefer in some cases ELCS. It has also been shown that in women with tokophobia the rst two stages of labour are prolonged by 30% resulting in increased medical interventions and medication, fetal di culties and EMCS [ 29 ], which has been shown to be responsible for a large percentage of postpartum posttraumatic stress disorder [ 30 ]. In our study, women with anxiety disorder or depression were more likely to have an EMCS, con rming the above ndings and revealing a de cit in perinatal mental health in Greece, due to a de cit in mental health services, lack of health professionals' appropriate training in addition to the stigma of mental illness which is a deterrent to access appropriate mental health services in Greece [ 31 ].…”
Section: Discusionmentioning
confidence: 99%